A retrospective study on drug interactions in Dr. Sardjito Hospital Yogyakarta - Fita Rahmawati; Rini Handayani; Vivi Gosal (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
The increasing number of drugs available and the increasing use of multidrug regimens which enhance the possibility for drug interactions. The aim of the study was to determine the frequency of drug-drug interaction and drug-food interaction both in outpatients and hospitalized patients. The research was also to determine the pattern of drug interaction mechanism and drugs which often show interaction.The Research type was descriptive. The data were conducted by retrospective, simple random sampling, taken from 90 samples of geriatrics patient hospitalized medical record in Interne medicine during June- September 2003, 120 samples of outpatient prescription took care from Haspita Farma Pharmacies during July-December 2003. Evaluation of the data was carried out descriptively.The result of the study showed that drug interaction occurred in 59% cases of hospitalized patient and 69% cases of outpatient. It was identified the existence of 125 drug interaction in hospitalized patient consists of 48 drug-drug interaction and 77 drug-food interaction. The pattern of drug interaction mechanism was pharmacokinetics pattern of drug interaction mechanism 36%, pharmacodinamic 16 % and unknown 48 %. The drug which often have interaction were furosemid, captopril, aspirin, and ceftriakson. In outpatient, It was identified 128 drug interactions consist of 47 drug-drug interactions case and 81 drug-food interaction. The mechanism pattern was pharmacokinetic 72%, pharmacodinamic 19% and unknown 11 %.The drug which often had interaction was phenitoin, phenobarbital, isoniasid, and rifampicin.Key words : drug interaction, Dr. Sardjito Hospital, Geriatric